A novel FGFR1-binding peptide attenuates the degeneration of articular cartilage in adult mice. Issue 12 (December 2018) - Tan, Q.; Chen, B.; Wang, Q.; Xu, W.; Wang, Y.; Lin, Z.; Luo, F.; Huang, S.; Zhu, Y.; Su, N.; Jin, M.; Li, C.; et al.
Summary: Objective: We previously reported that genetic ablation of (Fibroblast Growth Factors Receptors) FGFR1 in knee cartilage attenuates the degeneration of articular cartilage in adult mice, which suggests that FGFR1 is a potential targeting molecule for osteoarthritis (OA). Here, we identified R1-P1, an inhibitory peptide for FGFR1 and investigated its effect on the pathogenesis of OA in mice induced by destabilization of medial meniscus (DMM). Design: Binding ability between R1-P1 and FGFR1 protein was evaluated by enzyme-linked immuno sorbent assay (ELISA) and molecular docking. Alterations in cartilage were evaluated histologically. The expression levels of molecules associated with articular cartilage homeostasis and FGFR1 signaling were analyzed by quantitative real-time polymerase chain reaction (qRT-PCR), Western blotting and immunohistochemistry (IHC). The chondrocyte apoptosis was detected by terminal-deoxynucleoitidyl transferase mediated nick end labeling (TUNEL) assay. Results: R1-P1 had highly binding affinities to human FGFR1 protein, and efficiently inhibited extracellular signal-regulated kinase (ERK)1/2 pathway in mouse primary chondrocytes. In addition, R1-P1 attenuated the IL-1β induced significant loss of proteoglycan in full-thickness cartilage tissue from human femur head. Moreover, this peptide can significantly restore the IL-1β mediated loss of proteoglycan and type II collagen (Col II) and attenuate the expression of matrix metalloproteinase-13 (MMP13) in mouse primary chondrocytes. Finally, intra-articular injection of R1-P1 remarkably attenuated the loss of proteoglycan and the destruction of articular cartilage and decreased the expressions of extracellular matrix (ECM) degrading enzymes and apoptosis in articular chondrocytes of mice underwent DMM surgery. Conclusions: R1-P1, a novel inhibitory peptide for FGFR1, attenuates the degeneration of articular cartilage in adult mice, which is a potential leading molecule for the treatment of OA.